PHILOSOPHY OF LANGUAGE AND DIGITAL MEDIA: QUALITATIVE STUDIES IN THE FOREIGN LANGUAGE LEARNING PROCESS - Mimin Aminah; Zuriyati, Zuriyati; Samsi Setiadi (LPSDI Bina Patria, 2024)
The rapid evolution of digital technology has transformed foreign language learning, presenting both opportunities and challenges in understanding language meaning and cultural nuances. This qualitative study explores the role of digital media in the foreign language learning process through the lens of language philosophy, particularly Wittgenstein's language games and Searle's pragmatic theory. Data collected from 20 English education students through interviews and observations highlight the benefits of digital platforms such as Duolingo and YouTube in simplifying linguistic structures and facilitating interactive learning. However, respondents noted limitations in cultural depth and contextual nuance, reflecting the constraints of digital tools in conveying idiomatic expressions and non-verbal cues. The findings underscore the dual nature of digital media as both a facilitator and a constraint in language learning. While virtual platforms like Zoom enhance accessibility and collaborative learning, they often lack the emotional and cultural richness of face-to-face interactions. Respondents expressed optimism about future technologies, envisioning personalized learning environments driven by AI and immersive cultural experiences through virtual reality.The study emphasizes the need for educators to integrate project-based and interactive strategies that balance digital innovation with cultural and contextual engagement. For developers, the findings suggest a focus on adaptive technologies that simulate real-world linguistic and cultural interactions. These insights contribute to understanding language as a social construct mediated by technology, offering practical and theoretical pathways for advancing foreign language education in the digital age.